Tidal signatures in temperatures derived from daylight lidar soundings above Kühlungsborn (54°N, 12°E). (May 2015) - Kopp, M.; Gerding, M.; Höffner, J.; Lübken, F.-J.
Abstract: We have developed a new Rayleigh–Mie–Raman (RMR) lidar at the mid-latitude station in Kühlungsborn (54°N, 12°E) for analyzing geophysical phenomena at day and night, e.g., temperature tides and Noctilucent Clouds. For this study we have used about 3100 h of data since April 2011 with additional data from summer 2010. The RMR lidar was in operation day and night in addition to the existing daylight-capable potassium resonance lidar. We show for the first time an overview of the altitude structure and seasonal variation of temperature tides, observed with lidars between 40 and 100 km altitude at a mid-latitude site. There is a gap around 80 km altitude due to a decreasing signal-to-noise ratio during the day. We derive mean tidal amplitudes and phases with 24-, 12-, and 8-h period. In most of the months, the diurnal component dominates the other tidal components with mean amplitudes of 1–2 K in the stratopause region (45–55 km altitude), where it is up to three times higher than semidiurnal and terdiurnal tidal amplitudes. The diurnal tide is damped at ∼60 km altitude. In the mid-mesosphere (65–70 km) diurnal, semidiurnal, and terdiurnal tidal components have comparable mean amplitudes of about 1–1.5 K, except around the equinoxes. Around the mesopause the diurnal tide dominates again, with mean amplitudes of about 4 K, but with a large variability. The seasonal variation shows a conspicuous structure below ∼65 km altitude with tidal amplitudes small in summer and large around the equinoxes. This structure vanishes above ∼65 km. There, the amplitude increases in summer. The measured tidal amplitudes and phases are compared with the MERRA (Modern Era Retrospective analysis for Research and Applications) reanalysis data. Repeated soundings in subsequent years allow to examine the year-to-year variation. The data from March in both 2012 and 2013 show a prominent diurnal tide at around 45 km altitude with amplitudes about three times larger than in the other months. The short-term variability can be examined from continuous lidar operations during clear-sky periods. In a case study we show a large variability of the tidal amplitudes, especially the 8-h variation. This can only be examined due to a good temporal coverage of the lidar data. Abstract : Highlights: Height structure and seasonal variation of temperature tides by lidars, 40–100 km. New Rayleigh–Mie–Raman lidar for daylight soundings at Kühlungsborn (54°N, 12°E). Seasonal variation shows small tidal amplitudes in summer, large around equinoxes. Observed prominent diurnal tide in March three times larger than the annual mean. Examination of the short-term variability, large esp. for the terdiurnal tide.